PENINGKATAN KETERAMPILAN ARGUMENTASI ILMIAH SISWA MELALUI GUIDED INQUIRY LEARNING DALAM KONTEKS ISU KEBISINGAN YANG MENDUKUNG SDGS 3 - Luqyana Fadia, Allya; Bintang Ilhami, Fasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the improvement of argumentation skills through the Guided Inquiry Learning model with sound wave material integrated with the context of SDGs 3. The method used in this study is a quantitative method with a one-group pretest-posttest design on 30 students. The results of the study showed a significant increase in argumentation skills after the Guided Inquiry Learning model was applied to the sound wave material. This increase was shown in the results of the n-gain analysis which showed a moderate category. Students' argumentation skills in providing claims, showing evidence, and compiling warrants as support in order to strengthen their arguments. The application of this Guided Inquiry Learning model can be a strategy for developing innovative learning models for educators and students to continue developing their skills in arguing.